Double diffusive natural convection in power-law fluid saturated porous medium with Soret and Dufour Effects - Srinivasacharya,D. (2012)
The effects of double diffusive natural convection heat and mass transfer along a vertical plate embedded in a power-law fluid saturated Darcy porous medium in the presence of Soret and Dufour effects are studied. The governing partial differential equations are transformed into ordinary differential equations using similarity transformations and then solved numerically. A parametric study of the physical parameters involved in the problem is conducted and a representative set of numerical results is illustrated graphically.